Community Service (PKM) empowerment of kokoda tribem papuan community based on green mosque at Babul Jannah Mosque, Sorong - Rahman, Ainul Alim; Santoso, Budi; Zulkifli, Zulkifli; Muzdhalifah, Nirmalani; Bachtiar, Ahmad (Edumedia Solution, 2025)
The purpose of this Community Service activity is to provide clean water facilities based on science and technology at Masjid Hijau. This concept aims for environmental preservation, such as waste management as an effort to address climate change, as well as clean water management and education for teenagers and children, raising public awareness about the importance of waste management as an effort to tackle climate change, and 3) making mosques centers for community development. In its implementation, it is divided into two parts: workshops and green mosque practices. The hope is that after this service ends, the Babul Jannah Mosque in the Kokoda complex will truly implement the eco-mosque concept in mentoring the youth, making it a model for other mosques, especially those in Sorong City. For that reason, the community service program aims to provide clean water facilities and infrastructure, Green Mosque IPTEK training in well water filtration using the absorption method, training on the procedures, maintenance, and upkeep of clean filter equipment, character-building training for the Green Mosque, which includes environmental love, community IPTEK training on composting to produce fertilizer, equipping waste disposal facilities based on organic, inorganic, and hazardous waste categories, Trainer of Trainer training for mosque administrators to guide the youth and children around the mosque, and capacity-building for the mosque's BKM team. The training was with 18 participants out of 23 registered. The target of this activity is to gradually produce posters, HAKI, scientific journals, activity videos, and partner skill enhancement.